Peripheral neuromodulation in spasticity-plus syndrome: effects of pulsed radiofrequency on tonic-painful disorders in multiple sclerosis - Di Lorenzo, Luigi; D’Avanzo, Carmine (Frontiers in Neurology, 2025)
IntroductionSpasticity-Plus Syndrome (SPS) in multiple sclerosis (MS) represents a cluster of symptoms including spasticity, neuropathic pain, spasms, and bladder dysfunction. These manifestations may worsen after trauma or surgery. Pulsed radiofrequency (PRF) offers a minimally invasive neuromodulation strategy that could complement standard treatments.MethodsWe report the case of a 56-year-old woman with secondary progressive MS (EDSS 6.5) who developed SPS after hip arthroplasty. Despite multiple pharmacological therapies (baclofen, opioids, nabiximols), symptom control remained poor. Two diagnostic nerve blocks were performed, followed by PRF of the femoral and obturator articular branches. Outcomes were monitored using patient-reported measures, the Modified Ashworth Scale, and the Numerical Rating Scale.ResultsPRF induced a 50–60% reduction in pain and a marked decrease in spasms, with partial improvements in sleep and quality of life. The patient rated PRF as superior to all prior treatments. Benefits were sustained for several months, supporting repeat PRF and adjunctive nerve blocks during follow-up.DiscussionThis case illustrates the role of PRF in SPS management when pharmacological options are insufficient or poorly tolerated. PRF provides safe, repeatable peripheral neuromodulation without neuro-destructive effects, enabling multimodal, patient-centered care. Although based on a single case, these findings support the clinical value of the SPS construct and suggest PRF as a promising complementary strategy in MS-related disability.